-11-n=-11

Simple and best practice solution for -11-n=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11-n=-11 equation:


Simplifying
-11 + -1n = -11

Add '11' to each side of the equation.
-11 + 11 + -1n = -11 + 11

Combine like terms: -11 + 11 = 0
0 + -1n = -11 + 11
-1n = -11 + 11

Combine like terms: -11 + 11 = 0
-1n = 0

Solving
-1n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '-1'.
n = 0

Simplifying
n = 0

See similar equations:

| 3x+(x+38)=90 | | 14=5+h | | U-1=-4 | | -46=p-19 | | 8a-4-3a=12 | | 13-4x=-x-31 | | (x+54)+2x=90 | | 8x-4=-1 | | (x+54)+2x=180 | | 6(3x+5)=100 | | 6x+7c=37cforx | | 12x^2+105x+147=35 | | .2t+1.8=1.2 | | -.2t+1.8=1.2 | | 5x+(x-24)=180 | | .97n+5.95=11.57 | | 4(-8+5)=-32(0.44)-26 | | 0=7(6x-11)+2x+6 | | 5w-5=8w+16 | | 4(-8+5)=-32(3)-26 | | 16y^2+7y+10= | | x^3-x^2-x=-2x | | 1a^2-2a-7=0 | | 9x+-34=-88 | | 7x+28-4x-4=5 | | x=2mx-8b | | -5(5x-3)-27=-3(3x-2) | | 7b-4(3b+7)=7-(8+8b) | | -9x-16=-1 | | 5(x-3)=3x+4+2(5-x) | | .4t+1.7=1.3 | | 8y^2+105y+13= |

Equations solver categories